Key audit matters’ disclosure impact on investors’ reaction, audit quality and audit fees: Evidence from Europe - André, C.; Pais, C.; Oliveira, J. (45th Annual Congress of the European Accounting Association, 2023)
The present study investigates whether key audit matters (KAM) disclosure has an impact on investors’ reactions, audit quality, and audit fees. The article uses a sample that includes data from listed firms from the main stock market indices of each European Union’s country, from the two years after the transposition date of the requirements of Regulation No. 537/2014 to the national legislation of each state member. Main findings reveal that KAM’s disclosure has no impact on investors’ reactions, audit quality and audit fees. These findings can be explained by several reasons: investors may already be aware of the risks disclosed in KAM or they may believe that the auditor performed the necessary work to mitigate the disclosed risks; results from their impact on audit quality/audit fees may be driven from a lack of impact in the time resources and audit effort needed, and from auditors absorbing any additional time or audit effort related to KAM’s disclosure, respectively.